Advanced Glycation End Products in the Skin: Molecular Mechanisms, Methods of Measurement, and Inhibitory Pathways - Chen, Chun-yu; Zhang, Jia-Qi; Li, Li; Guo, Miao-miao; He, Yi-fan; Dong, Yin-mao; Meng, Hong; Yi, Fan (Frontiers in Medicine, 2022)
Advanced glycation end products (AGEs) are a series of stable compounds produced under non-enzymatic conditions by the amino groups of biomacromolecules and the free carbonyl groups of glucose or other reducing sugars commonly produced by thermally processed foods. AGEs can cause various diseases, such as diabetes, atherosclerosis, neurodegeneration, and chronic kidney disease, by triggering the receptors of AGE (RAGEs) in the human body. There is evidence that AGEs can also affect the different structures and physiological functions of the skin. However, the mechanism is complicated and cumbersome and causes various harms to the skin. This article aims to identify and summarise the formation and characteristics of AGEs, focussing on the molecular mechanisms by which AGEs affect the composition and structure of normal skin substances at different skin layers and induce skin issues. We also discuss prevention and inhibition pathways, provide a systematic and comprehensive method for measuring the content of AGEs in human skin, and summarise and analyse their advantages and disadvantages. This work can help researchers acquire a deeper understanding of the relationship between AGEs and the skin and provides a basis for the development of effective ingredients that inhibit glycation.